ASPALATHIN-RICH GREEN ROIBOS EXTRACT IN COMBINATION WITH GLYBURIDE AND ATORVASTATIN ENHANCES LIPID METABOLISM IN A db/db MOUSE MODEL - Patel, Oelfah; Muller, Christo; Joubert, Elizabeth; Rosenkranz, Bernd; Louw, Johan; Awortwe, Charles (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES This study investigated the effects of combining an aspalathin-rich green rooibos extract (GRT) with glyburide and atorvastatin in a type 2 diabetic (db/db) mouse model. METHODOLOGY Db/db mice were treated orally with glyburide and atorvastatin and GRT as mono and combination therapies for 5 weeks. An intraperitoneal glucose tolerance test was conducted at 3 weeks of treatment. Serum was collected for lipid analyses and liver tissues were collected for histological examination and gene expression. RESULTS There was an increase in the fasting plasma glucose (FPG) of the db/db compared to the lean mice (from 7.98 ± 0.34 to 26.44 ± 1.84, p<0.0001). GRT reduced FPG levels in db/ db mice when compared to untreated controls (from 26.44 ± 1.84 to 18.7 ± 4.4, p<0.001) without affecting bodyweight. Glyburide had no effect on FPG alone or in combination with GRT in db/db mice. Atorvastatin reduced cholesterol (from 4.00 ± 0.12 to 2.93 ± 0.13, p<0.05) and triglyceride levels (from 2.77 ± 0.50 to 1.48 ± 0.23, p<0.05). The hypo- triglyceridemic effect of atorvastatin was enhanced when combined with GRT and glyburide (from 2.77 ± 0.50 to 1.73 ± 0.35, p =0.0002). Glyburide reduced the severity and pattern of steatotic lipid droplet accumulation from a mediovesicular type across all lobular areas, whilst GRT with glyburide reduced the abundance and severity of lipid droplet accumulation predominantly in the centri- and mediolobular areas. GRT, glyburide and atorvastatin reduced the abundance and severity of lipid accumulation as well as the intensity score. CONCLUSION GRT or glyburide in combination with atorvastatin had no effect on blood glucose or lipid profiles, but a significant reduction in lipid droplet accumulation was observed.